2019
DOI: 10.1002/jez.2263
|View full text |Cite
|
Sign up to set email alerts
|

Conflict, compensation, and plasticity: Sex‐specific, individual‐level trade‐offs in green anole (Anolis carolinensis) performance

Abstract: Trade‐offs in performance expression occur because animals must perform multiple whole‐organism performance tasks that place conflicting demands on shared underlying morphology. Although not always detectable within populations, such trade‐offs may be apparent when analyzed at the level of the individual, particularly when all of the available data are taken into account as opposed to only maximum values. Detection of performance trade‐offs is further complicated in species where sexual dimorphism drives perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 79 publications
(121 reference statements)
2
11
0
Order By: Relevance
“…Indeed, diet‐restricted but protein‐supplemented, sprint‐trained animals exhibited both the greatest loss of mass and the largest decrease in bite force over the course of the experiment, but with no accompanying significant loss of sprint speed (Figure a,b). Our results for bite force plasticity match those of both Lailvaux et al () and Lailvaux et al () who found clear evidence of plasticity in male bite force in A. carolinensis . The lack of similar plasticity in sprint speed is therefore novel and represents scope for understanding the mechanisms whereby certain traits may be shielded against diminished expression associated with reduced resource availability.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Indeed, diet‐restricted but protein‐supplemented, sprint‐trained animals exhibited both the greatest loss of mass and the largest decrease in bite force over the course of the experiment, but with no accompanying significant loss of sprint speed (Figure a,b). Our results for bite force plasticity match those of both Lailvaux et al () and Lailvaux et al () who found clear evidence of plasticity in male bite force in A. carolinensis . The lack of similar plasticity in sprint speed is therefore novel and represents scope for understanding the mechanisms whereby certain traits may be shielded against diminished expression associated with reduced resource availability.…”
Section: Discussionsupporting
confidence: 92%
“…The results of our (admittedly crude) protein treatment notwithstanding, it is notable that sprint speed did not differ between lizards on a restricted diet and those on an ad libitum diet, emphasizing the seeming insensitivity of sprint speed to dietary restriction in A. carolinensis. This result is consistent with the ecology of green anoles, which exhibit low movement rates in nature characteristic of organisms that rely more on sprinting than on endurance (Irschick, 2000;Jenssen, Greenberg, & Hovde, 1995) and whose movement rates also are unaffected by sprint training (Husak & Lailvaux, 2019), and also with recent data showing that sprint speed shows significant repeatability in green anoles (Lailvaux, Cespedes, & Houslay, 2019). It is also unlikely that lizards in the diet-restricted groups were able to compensate for compromised sprint speed because of their lower body masses, as sprinting in lizards is not limited by power output (Farley, 1997; see also Irschick, Vanhooydonck, Herrel, & Andronescu, 2003).…”
Section: Discussionsupporting
confidence: 89%
“…Bite force is an important measure of whole‐organism performance that may differ between males and females (Gvozdík & Van Damme, 2003; Lailvaux, Cespedes, & Houslay, 2019; Lappin, Hamilton, & Sullivan, 2006; Lappin & Husak, 2005; Lappin & Jones, 2014; McLean et al, 2016). Some male iguanian lizards use their jaws as a weapon to fight other males or to intimidate and restrain female lizards (Lailvaux et al, 2019; Lappin & Husak, 2005; Lappin, Brandt, Husak, Macedonia, & Kemp, 2006; Lappin, Hamilton et al, 2006; McLean et al, 2016; McLean & Stuart‐Fox, 2015). In eastern collared lizards ( Crotaphytus collaris ), the bite force of adult males is a strong predictor of access to females, mating success, and genetic paternity, whereas body size is not; the greater bite force of males is associated with considerably greater head dimensions (likely related to having larger jaw muscles) than females (Husak, Lappin, & Van Den Bussche, 2009; Lappin & Husak, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Despite females having small claws when compared to males, claws might be larger than the optimal due to selection on the male trait (Husak & Swallow, ). If this is true, then we can expect compensation in the sex without the exaggerated trait as well (e.g., Cameron, Wynn, & Wilson, ; Lailvaux, Cespedes, & Houslay, ). Our data does not quite fit that expectation because females are faster than males.…”
Section: Discussionmentioning
confidence: 99%